1991
DOI: 10.1093/nar/19.20.5625
|View full text |Cite
|
Sign up to set email alerts
|

Effect pf 5-methylcytosine on the stability of triple-stranded DNA—a thermodynamic study

Abstract: We have previously shown that the pyrimidine oligonucleotide 5'CTTCCTCCTCT (Y11) recognizes the double-helical stem of hairpin 5'GAAGGAGGAGA-T4-TCTCCTCCTTC (h26) by triple-helix formation (1). In this paper, we report the effect on triplex formation of substituting the cytosine residues of Y11 with 5-methylcytosines (5meY11). In addition, we have studied the thermodynamics of the interaction between h26 and 5meY11. The results can be summarised as follows: (i) gel electrophoresis shows that at T = 5 degrees C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
165
1
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 201 publications
(181 citation statements)
references
References 27 publications
14
165
1
1
Order By: Relevance
“…These modifications have assisted in preventing the formation of unwanted intramolecular secondary structures within the TFOs. In the parallel pyrimidine triplex motif, the substitution of cytosine by 5-methylcytosine, N 6 -methyl-8-oxo-2-deoxyadenosine [52,53] or pseudoisocytodines [54] has been used to reduce the pH dependence of triplex formation. At neutral pH, the substitution of thymine by 5-propynyluracil stabilizes triplex formation [55].…”
Section: Chemical Modifications Of Tfosmentioning
confidence: 99%
“…These modifications have assisted in preventing the formation of unwanted intramolecular secondary structures within the TFOs. In the parallel pyrimidine triplex motif, the substitution of cytosine by 5-methylcytosine, N 6 -methyl-8-oxo-2-deoxyadenosine [52,53] or pseudoisocytodines [54] has been used to reduce the pH dependence of triplex formation. At neutral pH, the substitution of thymine by 5-propynyluracil stabilizes triplex formation [55].…”
Section: Chemical Modifications Of Tfosmentioning
confidence: 99%
“…Early studies with polymeric strands indicated an advantage in thermal stability with this substitution, 47,48 and more recent studies with short, well-defined sequences have confirmed a thermodynamic advantage as well. [49][50][51] One study found that the addition of each methyl group to uracil either in RNA or in DNA adds 0.1-0.5 kcal/mol of stability to double-and triple-helical structure. 51 It is thought that this effect is due to increased polarizability of methylated bases, which enhances van der Waals interactions with neighboring bases.…”
Section: A Addition Of Simple Substituents To Dna Basesmentioning
confidence: 99%
“…15,16 These limitations have been addressed by the incorporation of base and sugar modifications into pyrimidine TFOs. [17][18][19][20] On the contrary, TFOs form stable triplexes in the purine motif in a pH-independent manner. However, several groups have shown that binding of these guanine-rich (G-rich) TFOs to duplex DNA is significantly reduced at physiologic concentrations of monovalent cations, such as potassium (K + ).…”
Section: Introductionmentioning
confidence: 99%